IMF Governance-Summary of Issues and Reform Options. (Policy Papers; Policy Paper ;, 2009)
This paper summarizes the main governance challenges and reform options facing the IMF, drawing together the analysis and reform proposals in the reports of the Eminent Persons Group (headed by Trevor Manuel), the IEO, and a range of other recent work on Fund governance. Lest the wide scope of these inputs result in a laundry list, judgment has been exercised in selecting key issues and proposals, and in laying out some of the pros and cons. With reform of quotas/voting power on a separate track, the focus here is on the institutional framework through which members express voting power, weaknesses in which are seen by many to have eroded the Fund's legitimacy and effectiveness, thereby displacing the debate and initiative to outside entities. While an overall reform package would have to include quota shares, the key proposals discussed here aim to: increase political engagement and oversight; enhance Executive Board effectiveness and representation; modify voting rules; better delineate responsibilities; open up management selection; and tackle problems with mandate and institutional culture that limit the issues and approaches taken. Civil society has expressed a range of concerns related to IMF governance, including with regard to accountability at all levels (IMFC, Executive Board, management, and staff), mechanisms for responding to complaints and feedback from the broader public, and transparency. Given the diversity of their interests, and to provide unfiltered access to CSO views, the supplement: Fourth Pillar Recommendations from Civil Society; Preliminary Summary of Principles, Issues and Recommendations; has been prepared by CSO groups.